Combination of vasculature targeting, hypofractionated radiotherapy, and immune checkpoint inhibitor elicits potent antitumor immune response and blocks tumor progression. Issue 2 (9th February 2021) - Pierini, Stefano; Mishra, Abhishek; Perales-Linares, Renzo; Uribe-Herranz, Mireia; Beghi, Silvia; Giglio, Andrea; Pustylnikov, Sergei; Costabile, Francesca; Rafail, Stavros; Amici, Augusto; Facciponte, John G; Koumenis, Costantinos; et al.
Abstract : Background: Tumor endothelial marker 1 (TEM1) is a protein expressed in the tumor-associated endothelium and/or stroma of various types of cancer. We previously demonstrated that immunization with a plasmid-DNA vaccine targeting TEM1 reduced tumor progression in three murine cancer models. Radiation therapy (RT) is an established cancer modality used in more than 50% of patients with solid tumors. RT can induce tumor-associated vasculature injury, triggering immunogenic cell death and inhibition of the irradiated tumor and distant non-irradiated tumor growth (abscopal effect). Combination treatment of RT with TEM1 immunotherapy may complement and augment established immune checkpoint blockade. Methods: Mice bearing bilateral subcutaneous CT26 colorectal or TC1 lung tumors were treated with a novel heterologous TEM1-based vaccine, in combination with RT, and anti-programmed death-ligand 1 (PD-L1) antibody or combinations of these therapies, tumor growth of irradiated and abscopal tumors was subsequently assessed. Analysis of tumor blood perfusion was evaluated by CD31 staining and Doppler ultrasound imaging. Immunophenotyping of peripheral and tumor-infiltrating immune cells as well as functional analysis was analyzed by flow cytometry, ELISpot assay and adoptive cell transfer (ACT) experiments. Results: We demonstrate that addition of RT to heterologous TEM1 vaccination reduces progression of CT26 and TC1 irradiated and abscopal distant tumors as compared with either single treatment. Mechanistically, RT increased major histocompatibility complex class I molecule (MHCI) expression on endothelial cells and improved immune recognition of the endothelium by anti-TEM1 T cells with subsequent severe vascular damage as measured by reduced microvascular density and tumor blood perfusion. Heterologous TEM1 vaccine and RT combination therapy boosted tumor-associated antigen (TAA) cross-priming (ie, anti-gp70) and augmented programmed cell death protein 1 (PD-1)/PD-L1 signaling within CT26 tumor. Blocking the PD-1/PD-L1 axis in combination with dual therapy further increased the antitumor effect and gp70-specific immune responses. ACT experiments show that anti-gp70 T cells are required for the antitumor effects of the combination therapy. Conclusion: Our findings describe novel cooperative mechanisms between heterologous TEM1 vaccination and RT, highlighting the pivotal role that TAA cross-priming plays for an effective antitumor strategy. Furthermore, we provide rationale for using heterologous TEM1 vaccination and RT as an add-on to immune checkpoint blockade as triple combination therapy into early-phase clinical trials.